2019
DOI: 10.5498/wjp.v9.i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity of bipolar and anxiety disorders: An overview of trends in research

Abstract: Over the last three decades burgeoning research has shown that anxiety disorder comorbidity is not only highly prevalent in bipolar disorder (BD), but it also adversely impacts the course, outcome, and treatment of BD. The present review provides an overview of the current trends in research on comorbid anxiety and BDs based on prior reviews and meta-analyses (n = 103), epidemiological surveys, and large-scale clinical studies. The results reiterated the fact that at least half of those with BD are likely to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
47
2
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 157 publications
(271 reference statements)
7
47
2
5
Order By: Relevance
“…These findings are consistent with previous studies from the SARS epidemic, which reported higher levels of anxiety in inpatients with schizophrenia compared with the staff ( Iancu et al, 2005 ), but this reaction was not more severe than in people with other common mental disorders in our sample. The existing literature found that anxiety, a frequent yet often neglected comorbidity in SMD ( Buonocore et al, 2018 ), could lead to a worse prognosis in both BD ( Corry et al, 2013 ; Spoorthy et al, 2019 ) and schizophrenia ( Braga et al, 2013 ). While other people may be able to develop functional coping strategies to face this emotional reaction, anxiety could determine unfavorable outcomes in the vulnerable population with SMD, such as triggering a relapse ( Druss, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with previous studies from the SARS epidemic, which reported higher levels of anxiety in inpatients with schizophrenia compared with the staff ( Iancu et al, 2005 ), but this reaction was not more severe than in people with other common mental disorders in our sample. The existing literature found that anxiety, a frequent yet often neglected comorbidity in SMD ( Buonocore et al, 2018 ), could lead to a worse prognosis in both BD ( Corry et al, 2013 ; Spoorthy et al, 2019 ) and schizophrenia ( Braga et al, 2013 ). While other people may be able to develop functional coping strategies to face this emotional reaction, anxiety could determine unfavorable outcomes in the vulnerable population with SMD, such as triggering a relapse ( Druss, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other psychiatric disorders characterized by a spectrum of symptom severity and shared variance (e.g., schizophrenia, mood, and anxiety; 13,14), individual variation in ASD goes beyond core diagnostic symptoms (i.e., impairment in social communicative skills, restricted/repetitive behaviors/interests) and associated psychopathology (15,16). In particular, ASD is often complicated by accompanying heterogeneity in the type of onset (9), language skills (17, 18), intellectual abilities (19), and medical conditions (20).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other psychiatric disorders characterized by a spectrum of symptom severity and shared variance (e.g., schizophrenia, mood, and anxiety; 13,14), individual variation in ASD goes beyond core diagnostic symptoms (i.e., impairment in social communicative skills, restricted/repetitive behaviors/interests) and associated psychopathology (15,16). In particular, ASD is often complicated by accompanying heterogeneity in the type of onset (9), language skills (17, 18), intellectual abilities (19), and medical conditions (20).…”
Section: Introductionmentioning
confidence: 99%